(untitled) (Verba Vitae Unwira, 2020)
Politeness in Using Tentun Language in the interpersonal communication between Rafa’e Communities and Royals This study examines the uniqueness of Tetun Language in Timor. By applying descriptive-qualitative method and supported by Herbert Mead’s Symbolic Interactionalism Theory, this study has successfully uncovered several unique items of this language. Tetun Language is one of the dozens of dialects found on the island of Timor. The Tetun language, is generally spoken by the speaking community in Timor Leste and in the Belu district and Malacca district in the region of Indonesia. This study intends to examine social stratification based on Tetun language speech criteria, speech levels in Tetun culture, and politeness of communication with nobles in Tetun culture. The subject is analyzed with the perspective of Symbolic Interactionism theory and descriptive-qualitative methodology. The results of the study indicate that the Tetun language is still maintained by the speaking communities in the Belu and Malacca regions, especially the RafaE-Kagamatan Raimanuk-Belu District, in terms of their stiffness and authenticity, including: vocabulary, grammar, syntax, morphology, phonology, conjugation and ethics- moral, namely politeness in Tetun. Because Tetun Language has three levels of speech and in its use, speakers can choose the right words adapted to speech partners who come from three different social stratifications: people can speak ordinary civilizations, people participate in customary civilizations, people speak of royal civilization.